Propositional Attitude Verbs And Complementizers In Medumba - Gatchalian, Terrance; Lee, Rachel; Tyrchan, Carolin (My University, 2022)
We present the preliminary results of an investigation on complementizers and their interaction with propositional attitude verbs in Medumba (Grassfields Bantu, Niger-Congo). This initial sketch of the Medumba C-system opens up questions about the syntactic distribution and semantic force of the various Cs. There are two clause-initial Cs, /mbʉ/ and /ndà/, of which /mbʉ/ has three syntactically conditioned allomorphs: [mbʉ̀ ]-L, [mbʉ́ ʉ̀ ]-HL and [mbʉ̀ ʉ́ ]-LH. The clause-final [lá] obligatorily co-occurs with two of the clause-initial Cs, namely [mbʉ́ ʉ̀ ]-HL and [ndà]. Additionally, the inventory of propositional attitude verbs (pavs) is quite small, with only four identified thus far: two are monomorphemic ([lεn] ‘know’, [t͡ʃúp] ‘say’) and two are are bi-morphemic ([kwὲ-də̀ ] ‘think-iter’, [bέt-tə́ ] ‘askiter’). We make the case for a syntactically conditioned floating H-tone. Additionally, we propose a basic structure of the Medumba CP and raise questions about the scope of polarity and the nature of the clause-final particle /lá/.
Keywords: Medumba; propositional attitude; embedding